Gut Microbiota Types between Well-Grown and Stunted Children: A Systematic Review - Eriyanti Astika; Ahsanal Kasasiah; Jekmal Malau; Al Mukhlas Fikri (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2024)
Stunting, one of the malnutrition in the prenatal period up to the first two years of life and often exacerbated by recurrent gastrointestinal infections after birth. This study explores from various databases including Pubmed, Scopus, Science Direct, Sage Journal, Springer Link, with keywords: "stunting, gut microbiota, toddler". In this study, 10 open access articles published in 2016-2024 were used as sources of information using PRISMA 2020 guideline. It was found that the presence of gut microbiota plays a role in stunting. Gastrointestinal infections have specific mechanisms that can lead to impaired growth and postnatal growth. Deficiency of non-pathogenic gut microbiota is considered to be the main cause. Changes in gut bacterial composition in children under five are associated with increased gastrointestinal frequency, which in turn leads to chronic growth disorders.